PENGARUH PENJUALAN BERORIENTASI PELANGGAN, KUALITAS HUBUNGAN PENJUAL PEMBELI, DAN PERILAKU PENJUALAN ADAPTIF UNTUK MENINGKATKAN KINERJA TENAGA PENJUAL (Studi Kasus Pada Tenaga Pemasar Keagenan PT Prudential Life Assurance Kota Semarang) - Muftiasa, Iqbal; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2018)
This study aims to analyze customer-oriented starters on buyer seller relationship quality and adaptive sales behavior and its impact on salesperson performance. This study was taken with a sample of 130 respondents who have been selected. Respondents are salespeople at PT Prudential Life Assurance Kota Semarang. The analytical technique used to process the data is Structural Equation Modeling (SEM) which is run with software from AMOS version 22. Method of data collection using probability sampling. The model of the study has met the rules of Goodness of fit criteria, among which are: Chi Square (121,985), probability (0.058), RMSEA (0,042), CMIN / DF (1,232), TLI (0,934) and CFI (0,946). The results of the analysis show that customer-oriented prefixes have a positive and significant effect on the quality of the buyer's seller relationship and the adaptive sales behavior, but have no effect on the performance of salespeople. While the buyer seller relationship quality and adaptive sales behavior have a positive and significant influence on the performance of salespeople. The quality of the buyer's seller relationship is the variable that has the greatest influence on the performance of salespeople that is equal to 1.586; while the adaptive sales behavior variable has an influence on the performance of salespeople of 0.177.The conclusion of this research is the implementation of customer-oriented sales proved to have a positive influence that can improve the performance of salespeople by through the quality of buyer's seller relationship and adaptive sales behavior.